Development and evaluation of diverse wilt resistant monoecious lines in castor: Development and evaluation of diverse wilt resistant monoecious lines in castor - T MANJUNATHA; C LAVANYA; M SANTHALAKSHMI PRASAD; S SENTHILVEL; A J PRABAKARAN; G BALAKISHAN; A VISHNUVARDHAN REDDY (Journal of Oilseeds Research, 2020)
Since 1990s, development of wilt resistant and high yielding hybrids has played an important role in increasing the productivity of castor from around 320 kg/ha to 1700 kg/ha. Eleven elite monoecious lines having wilt resistance were developed by hybridization using five germplasm and seven elite monoecious lines. The elite lines viz., ICS- 303, ICS-304, ICS-315 and ICS-318 had better yield traits like spike length, seed weight and seed yield per plant. ICS-320 and ICS-321 derived from 48-1 and RG-2991 had the highest oil content (>50%) than the checks 48-1 and DCS-107. These elite lines will help in development of wilt resistant and high yielding hybrids and varieties in castor.